2004
DOI: 10.1080/02652030310001647217
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the use of semicarbazide as a metabolic target of nitrofurazone contamination in coated products

Abstract: Data from the Brazilian Agricultural Ministry show that before the implementation of the Brazilian programme of nitrofuran control in February 2003, the cases of contamination of Brazilian chicken by nitrofurans were almost exclusively due to furaltadone. After May 2003, such cases decreased until no more reports of Brazilian chicken contamination with this nitrofuran were reported. Curiously, after April 2003, an increase was observed in the numbers of contaminated samples by semicarbazide, the target metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 8 publications
2
38
0
Order By: Relevance
“…(Becalski, Lau, Lewis, & Seaman, 2006;K Hoenicke, Gatermann, Hartig, Mandix, & Otte, 2004;Stadler et al, 2004). SEM is also believed occur naturally in some crustaceans such as prawns, crabs and shrimp (Katrin Hoenicke & Gatermann, 2006;Pereira, Donato, & De Nucci, 2004). As a result, the use of SEM as a definitive marker for the monitoring of nitrofurazone misuse is debatable.…”
Section: Discussionmentioning
confidence: 96%
“…(Becalski, Lau, Lewis, & Seaman, 2006;K Hoenicke, Gatermann, Hartig, Mandix, & Otte, 2004;Stadler et al, 2004). SEM is also believed occur naturally in some crustaceans such as prawns, crabs and shrimp (Katrin Hoenicke & Gatermann, 2006;Pereira, Donato, & De Nucci, 2004). As a result, the use of SEM as a definitive marker for the monitoring of nitrofurazone misuse is debatable.…”
Section: Discussionmentioning
confidence: 96%
“…However, the presence of SC in meat may originate from other sources than from the use of the parent drug nitrofurazone. Pereira et al [14] demonstrated that some meats coated with flour were contaminated with SC, the origin of which was due to azodicarbonamide used in the cereal industry as a dough maturing and bleaching agent. Furthermore, SC has also been found in foods after treatment with sodium hypochlorite, related to certain food processing methods used for disinfection or bleaching [15].…”
Section: Analysis Of Incurred Meatsmentioning
confidence: 98%
“…Methods for the determination of semicarbazide presence or contamination not related to nitrofuran abuse in matrices such as carrageenan and algae (Hoenicke et al, 2004), shrimp (Bock et al, 2007b), crayfish (Saari and Peltonen, 2004) flour (Becalski et al, 2004), salt (Pereira et al, 2004) and baby food (De Souza et al, 2005) have also been established.…”
Section: Sample Preparation Methodsmentioning
confidence: 99%
“…Hypochlorite is commonly used for carrageen bleaching or water disinfection and also as a disinfectant during egg breaking procedures (de la Calle and Anklam, 2005). SEM has also been found to occur naturally in particular crustaceans such as shrimp, prawn, and crab, generating queries over its suitability as a marker for detection purposes in these species (Pereira et al, 2004;Saari and Peltonen, 2004;Hoenicke and Gatermann, 2006).…”
Section: Sources Of Nitrofuran and Semicarbazide Contaminationmentioning
confidence: 99%